Assessing vulnerability of buildings to hydro-meteorological hazards using an expert based approach – An application in Nehoiu Valley, Romania. (September 2015) - Godfrey, A.; Ciurean, R.L.; van Westen, C.J.; Kingma, N.C.; Glade, T.
Abstract: As the number of reported natural disasters resulting in casualties and damages increases worldwide, assessing vulnerability of the built environment represents a fundamental step towards reducing the probability of loss. This is a challenge in areas where data are sparse, and where no vulnerability curves exist for different building types. The aim of this paper is to develop a new expert based approach that allows physical vulnerability assessment of buildings to hydro-meteorological hazards in areas with limited information about the hazard or the exposed elements. The methodology is based on three steps: firstly, a vulnerability index is calculated based on expert weighing of vulnerability indicators using Analytical Hierarchy Process analysis. Secondly, a set of vulnerability curves is selected from the literature and a generic vulnerability curve is calculated as the average of these input functions. Lastly, the vulnerability index together with the generic vulnerability curve is used to generate a specific vulnerability curve representative for the studied area. The applicability of this approach is demonstrated in Nehoiu Valley, Romania. The results show that vulnerability indices for the 60 sampled buildings vary between 0.2 and 0.6 for all hazard types, and no buildings exhibit indices lower than 0.2 for debris flows or slow moving landslides. The specific curves show generally lower values of degree of loss for similar inundation depths compared with the general vulnerability curve. The proposed methodology exploits two vulnerability models in a new, complementary manner and it can be used for decision-making support in disaster response and risk management.